Experience of Nurses in Implementing Patient Safety Culture at USU Hospital - Zuraidah Zuraidah; Nurmaini; Roymond H. Simamora (Dunia Keperawatan: Jurnal Keperawatan dan Kesehatan, 2022)
A holistic patient safety program requires a crucial and fundamental component: patient safety culture. It is also critical in the evaluation of hospital safety and service quality. The purpose of the study was to find out how nurses at USU Hospital implemented a patient safety culture. The Collaizzi approach to descriptive phenomenology was applied in the study design. Purposive sampling was used to choose fifteen participants who met the inclusion criteria. In-depth interviews were used to acquire the information. Verbatim description was used in the analysis and interpretation. Five themes emerged from the study, namely: (1) accomplishment of patient safety goals with the support from the hospital management, (2) information provision about patient nursing care to improve patient safety, (3) report of patient safety incidents, (4) obstacles encountered by nurses in implementing patient safety culture, and (5) expectation that nurse implement safety culture. It suggested that nursing services facilitate nurses with training on patient safety culture regularly to improve their behaviors in reporting any patient safety incidents.